Long-Standing Persistent Atrial Fibrillation Ablation: How Do You Perform? Left and Right Atrial Linear Ablation in Addition to Pulmonary Vein Isolation - Brunelli, Michele; Sammut, Mark Adrian (JOURNAL OF CARDIAC ARRHYTHMIAS, 2020)
Catheter ablation of long-standing persistent atrial fibrillation is not yet clearly defined with respect to endpoints, and different ablative strategies are offered to patients. Presented here is an approach aiming at biatrial debulking in the form of extensive linear ablation, specifically targeting areas of low-voltage complex fractionated electrograms, in addition to pulmonary vein isolation. Its main advantage is that it is not dependent on operator/system variability, since the strategy of isolating the pulmonary veins, superior vena cava and left atrial posterior wall together with achievement of bidirectional block during linear ablation provides objective endpoints that can consistently be reproduced.